Association between shift work and periodontal health in a representative sample of an Asian population - Han, Dong-Hun; Khang, Young-Ho; Jung-Choi, Kyunghee; Lim, Sinye (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVE ': 'The association of shift work with periodontal disease is not well known. We studied the relationship between shift work and periodontitis in a representative sample of an Asian population. ' ' METHODS ': 'Participants were 4597 full-time employees from the Fourth Korean National Health and Nutrition Examination Survey (KNHANES IV). Shifting patterns were categorized into five shifts: daytime (N=3768), evening (N=121), night (N=59), rotating (N=206), and irregular (N=443). Periodontitis was measured with the Community Periodontal Index (CPI). Confounders included age, gender, income, and education. Mediators were frequency of daily tooth brushing, regular dental check-up, smoking, alcohol consumption, diabetes, obesity, and white blood cell count. Multiple logistic regression analyses were performed to evaluate the relationship. ' ' RESULTS ': 'The prevalence of periodontitis in the study population was 32.3%. Shift workers had an elevated odds ratio (OR) of periodontitis [OR 1.22, 95% confidence interval (95% CI) 1.01–1.48] after controlling for confounders. The magnitude of the association between shift work and periodontitis attenuated with adjustment of mediators (smoking and a marker of inflammation). In subgroup analyses, the association was significant (OR 1.42, 95% CI 1.03–1.95) among those ≥45 years. Irregular shift among those ≥45 years showed a significant association (OR 1.79, 95% CI 1.15–2.78). ' ' CONCLUSION ': 'Findings of this cross-sectional study suggest that shift work may be associated with periodontitis. Shift workers aged ≥45 years and irregular shift workers aged ≥45 years were risk groups for periodontitis.
Keywords: Asia; epidemiology; inflammation; Korea; peridontal health; periodontitis; shift work